O trabalho docente na sociedade da informa????o: possibilidades e desencantos - Silva Neto, Urbano Gomes da (2017)
This paper proposes an analysis of how information occupies central space in contemporary society and the consequences for the exercise of teaching. At first one could expect a valuation of the workers in education. However, what is perceived is an increase in pressure under these professionals affecting them in the emotional field, causing stress, depression, shame and professional exhaustion - Burnout Syndrome. The worker in the area of education is in search of the construction of identity and physical and psychic integrity. However, in many situations they are faced with suffering due to lack of communication at work, with poor social relations at work, lack of professional achievement, among other factors. Thus, the present research points to the importance of understanding the physical, psychic and social consequences generated by the information society in teachers and their educational practices.